2022
DOI: 10.2196/32558
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mental Health Professionals’ Perspectives and Practices Regarding the Implementation of Digital Mental Health: Qualitative Study

Abstract: Background Despite the potential of digital mental health to provide cost-effective mental health care, its adoption in clinical settings is limited, and little is known about the perspectives and practices of mental health professionals regarding its implementation or the factors influencing these perspectives and practices. Objective This study aims to characterize in depth the perspectives and practices of mental health professionals regarding the im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 71 publications
(122 reference statements)
1
25
0
Order By: Relevance
“…In this recent study (Mendes-Santos et al, 2022), the participants mentioned the importance of setting up the physical space of the room from where the session is occurring considering the flow and confidentiality of the session, the lighting and camera position, and the use of an ethernet cable for connection stability, which is in line with the guidelines presented in this review. Furthermore, both the difficulty and the importance of establishing clear therapeutic boundaries are also mentioned in recent studies (Dores et al, 2020;James et al, 2022;Mendes-Santos et al, 2022;Simpson et al, 2021). The online provision of psychological services demands boundaries to be flexible enough to benefit from the advantages of the remote environment but also stable and clearly stated in a therapeutic contract to avoid transgressions (Simpson et al, 2021).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In this recent study (Mendes-Santos et al, 2022), the participants mentioned the importance of setting up the physical space of the room from where the session is occurring considering the flow and confidentiality of the session, the lighting and camera position, and the use of an ethernet cable for connection stability, which is in line with the guidelines presented in this review. Furthermore, both the difficulty and the importance of establishing clear therapeutic boundaries are also mentioned in recent studies (Dores et al, 2020;James et al, 2022;Mendes-Santos et al, 2022;Simpson et al, 2021). The online provision of psychological services demands boundaries to be flexible enough to benefit from the advantages of the remote environment but also stable and clearly stated in a therapeutic contract to avoid transgressions (Simpson et al, 2021).…”
Section: Discussionmentioning
confidence: 52%
“…Studies have been pointing to these two topics both as difficulties that are reported by psychologists (Dores et al, 2020) and as factors that shall be considered prior to and during remote psychological sessions (Mendes-Santos et al, 2022;Simpson et al, 2021). In this recent study (Mendes-Santos et al, 2022), the participants mentioned the importance of setting up the physical space of the room from where the session is occurring considering the flow and confidentiality of the session, the lighting and camera position, and the use of an ethernet cable for connection stability, which is in line with the guidelines presented in this review. Furthermore, both the difficulty and the importance of establishing clear therapeutic boundaries are also mentioned in recent studies (Dores et al, 2020;James et al, 2022;Mendes-Santos et al, 2022;Simpson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Looking at the studies mentioned, it can be seen that Internet-based interventions can be as effective as face-to-face interventions (30). Nowadays, using smartphones, while saving time and being cost-effective, can be a great alternative to face-to-face health promotion programs (31).…”
Section: Discussionmentioning
confidence: 99%